2007
DOI: 10.1590/s1519-69842007000200009
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of the Green-cheeked parakeet (Pyrrhura molinae) in dry forests in western Brazil

Abstract: The genus Pyrrhura includes small to medium-sized parakeets, which inhabit both low and dry alongside tall rainforests, mainly in South America. Pyrrhura molinae is still common, year round, in the markedly seasonal forests of western Brazil. This parakeet, as well as most Neotropical parrots, continues to be poorly understood. Hence, in the present study I examined their foraging ecology both in a highly deciduous and in a semi-deciduous forest in western Brazil. In addition, I assessed the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…Among them, we highlight the fig tree (Ficus spp. ), that are a remarkable food resource for frugivores, mainly in periods of fruit scarcity, as has been highlighted in several studies in various parts of the world (Terborgh, 1986;Lambert and Marshall, 1991;Shanahan et al, 2001;Ragusa-Netto, 2002, 2007Tello, 2003). However, another authors found different results in their studies and not confirmed the key role of these species (Gautier-Hion and Michaloud, 1989;Kattan and Valenzuela, 2013).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Among them, we highlight the fig tree (Ficus spp. ), that are a remarkable food resource for frugivores, mainly in periods of fruit scarcity, as has been highlighted in several studies in various parts of the world (Terborgh, 1986;Lambert and Marshall, 1991;Shanahan et al, 2001;Ragusa-Netto, 2002, 2007Tello, 2003). However, another authors found different results in their studies and not confirmed the key role of these species (Gautier-Hion and Michaloud, 1989;Kattan and Valenzuela, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…Species that produce leaves, flowers or fruits during periods of low resource availability may be considered important food producers for fauna (Terborgh, 1986;Shanahan et al, 2001;Ragusa-Netto, 2006;2007). Among them, we highlight the fig tree (Ficus spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These birds are well known by tracking the erratic pattern of fruit availability (Renton, 2001, Moegenburg andLevey, 2003;Ragusa-Netto, 2007a, b, 2008; consequently, the proportional crop loss to them may vary according to food resources availability (Schupp, 1988(Schupp, , 1990Peres, 1991). In fact, parrots are assumed as important seed predators due to their large and mobile populations (Terborgh et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Dentre os consumidores de embaúbas encontram-se mamíferos, aves, peixes e insetos, sendo os relatos mais recorrentes para o primeiro grupo. 2,[34][35][36][37][38][39] No Brasil, os mamíferos frugívoros estão entre os principais consumidores de embaúbas. Entre os primatas, as espécies dos gêneros Alouatta (bugio) e Cebus (macacoprego), assim como entre os Chiroptera as espécies do gênero Artibeus, possuem o maior número de consumidores.…”
Section: Introductionunclassified